Comparative analysis of surgical outcomes of traditional laparotomy and minimally invasive technologies in the treatment of liver echinococcosis - Butaboev , Jasurbek; Shaykhova , Guli; Qosimov , Adham (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Epidemiological metrics indicate a persistently high surgical burden associated with cystic echinococcosis in endemic regions, demanding rigorous evaluations of operative trajectories. The current investigation analyzes the multidimensional dynamics of surgical outcomes, comparing traditional open laparotomy against minimally invasive techniques (laparoscopic echinococcectomy and PAIR) in the management of hepatic hydatidosis. The study population comprised 210 adult patients diagnosed with hepatic echinococcosis, systematically monitored utilizing a prospective cohort architectural design over a 48-month period. Empirical clinical data demonstrate a robust inverse correlation between the application of minimally invasive modalities and the incidence of severe postoperative morbidity. Analytical outputs confirm that integrating laparoscopic protocols optimizes intraoperative hemodynamics, yielding a significant reduction in mean intraoperative blood loss to 125 +/- 35 mL, compared to 430 +/- 85 mL in the laparotomy cohort. The dynamics of the obtained results mandate an urgent paradigm shift toward organ-preserving, low-trauma interventions. Patients subjected to minimally invasive approaches exhibited a drastically reduced duration of hospital stay (5.2 +/- 1.4 days versus 12.8 +/- 2.6 days) and a drop in overall localized complications, including biliary fistulas, from 18.1 percent to 5.7 percent. These findings fundamentally bridge persistent literature gaps by validating a comprehensive surgical safety model, establishing a rigorous foundation for modernizing hepatobiliary protocols and significantly enhancing long-term patient recovery trajectories.